PERAN PERPOLISIAN MASYARAKAT DALAM MENANGANI MASALAH KEKERASAN DALAM RUMAH TANGGA GUNA TERWUJUDNYA PERLINDUNGAN HUKUM - Yustinus Bowo Dwinugroho; Lilik Mulyadi; Suryawan Raharja (Kajian Hasil Penelitian Hukum, 2018)
Indonesian   National  Police  is  an  executive  agency  engaged  in  the   forefront  in handling  legal cases in  accordance  with  the  Act. Domestic  violence  domestic violence  once  considered a myth  and  personal  matter now the  facts  and  realities  of  domestic  life  and into  the  public domain. Most  victims of domestic violence  are  women  and  the  perpetrator  is  the  husband.  Perpetrators  or  victims of   domestic     violence     are    people     who    are    related    by   blood,    marriage,   dairy, care, guardianship   with  her   husband  and  children  and  even a  housekeeper. Ironically  domestic violence     cases   are    often  covered   up   by  the   victim  due  to  the  structure adrift cultural, religious and legal systems that are not ye tunderstood.The   focus  of  research  in  the preparation  of   the  article  is limited to the  basic tasks and the  implementation  of   community  policing  in  the  area  of Yogyakarta  police-related  duties and   functions  as   well  as   systems  and  methods  of   community  policing  duties. The  type of research   is   qualitative   descriptive   informants   were  9  people.  Data   collection    included   interviews,  observation  and   documentation.  technical  analysis  of  data is  performed through three  phases  namely  data  collection, data  identification, data   interpretation  and  conclusion.        The   research   concludes   that   community   policing  in  moving  the community to play an active  role  in  creating an  environment  that  is  safe, peaceful  and  serene  as  well  as  play an active   role  in   preventing  acts  of  domestic  violence  through an  sociological  approach  that targets   individuals,  families,   neighborhoods,  villages  wards,   educational   Institutions  and  organizations   community.  Policing   in    partnership   with   the    community    and   make   the  community   as  a subject   to  maintain   security   and  prevent  acts  of domestic violence is very  effective. Open  space  for  dialogue  for all  family  members  to  solve problems without violence so    that   they  can  build  a collective  consciousness  of  every  community  member  to create a harmonious family environment is based on an attitude of love and affection.